Analysis of Entrepreneurship Values in Islamic Education Learning and Morals at Al Alif Vocational High School - Adib, Hamdan; Intania, Naila (EDUKASIA, 2022)
The implementation of learning Islamic Religious Education and Morals at Al Alif Blora Vocational School turns out to have entrepreneurial value in it which is the basis for carrying out this research. This research is a field research with a qualitative approach. Data obtained through non-participatory observation, semi-structured interviews and documentation with data analysis utilizing Miles and Huberman's theory. The results of this study indicate that the learning carried out at SMK Al Alif Blora contains several entrepreneurial values, namely the core activities in the form of the values of Independence, self-confidence, originality, creativity, and courage in taking risks. Then in the closing activity there are values of confidence, originality, and result oriented. Evaluation activities also have entrepreneurial values in them, namely self-confidence through assignments that must be done independently in the form of writing, photos and videos in order to bring independence to students. Human-oriented values, namely giving assignments by giving assignments in groups with the demand for cooperation between students in order to raise awareness that humans are social creatures and originality as seen from the follow-up activities given by the teacher to students.